Interlanguage Error Made By Students In Writing Recount Text (A Study At Man 2 Boyolali) - HIDAYATULLAH, SYARIF; , Dr.Anam Sutopo, M.Hum (2014)
This study analyzes interlanguage errors of 60 written text by 60 students. The participants are eleventh grade students of MAN 2 Boyolali. All of the participants are from non-English speaking background and scarcely communicate in English in outside of the school. The object of this study was students' recount text. The researcher bounds the study of error based on the linguistic category taxonomy and surface strategy taxonomy to investigate the data made by the subjects. All of the errors in the texts were identified and classified into various categorizations. The results of the study show that three categories errors executed by the participants were morphological error (bound morpheme, noun, verb, adjective, false friend, code switch, spelling and pronoun), syntactical error (tenses, phrase, sentence and article) and discourse error (reference, generic structure and conjunctive). In order to find out the total number of errors as well as the frequency of the occurrence of each type of errors, all types of errors are then calculated. The writer finds 337 erroneous. The highest percentage of errors recorded is in morphological area 160 errors (47.47%), the second is in syntactical field 153 errors (45.40%) and the lowest percentage of errors is in discourse subject 24 errors (7.12%). The writer reaches the conclusion from this study that the dominant error made by students is in morphological. The teachers should make the students realize about the differences between Indonesian and English structures, because it may make the process of acquiring the native language more difficult and complicated for the students. By doing error analysis, teachers will acquire knowledge about the students' errors in writing process. After doing this, the teacher can predict the errors which will be made by the students. Since the students' errors are valuable feedbacks for teacher, it makes the teacher can get the learner s' progress in their skill.